Evaluating CALL in Higher Education Institutions - Karmila Machmud (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2020)
The goal of this research is to elaborate on the implementation of CALL subject in English as a Foreign Language Instructions at a higher education level. As one of the four pillars of a university’s development program, the use of ICT in the teaching and learning process has gained significant attention from higher education institutions; thus, through this research, the integration of CALL subject in English education curriculum and instruction is designed. The design then offered to be implemented in the English education program at a higher education level. Studies in CALL field have developed significantly in determining the effect of the technology use in language learning; thus, it is considered significant to be included in the English Education curriculum. This research is targeting the mastery of technology by student teachers’ literacy to prepare them for becoming English teachers who understand the technology and able to use it in the instructions setting. This is important considering that the students nowadays are born in the technology era. This paper discusses the implementation process of the CALL subject and the perspectives of EFL teachers and students towards the subject.